Bagaimana Keberlanjutan Zakat dan Dampak Makroekonomi dalam Mengurangi Pengangguran: Peran Zakat dan Variabel Makroekonomi dalam Mengurangi Pengangguran di Indonesia - Indirwan, Syanisma Khansa; Suprayitno, Aryadimas; Asya'bani, Nispia; Rusgianto, Sulistya (Transformatif, 2025)
This study examines the short- and long-term impacts of inflation, economic growth, and zakat on unemployment in Indonesia, utilizing quarterly time-series data from 2011Q1 to 2022Q4. The unemployment rate serves as the dependent variable, while the independent variables comprise inflation, Gross Domestic Product (GDP), and total zakat distribution. The analysis employs the Vector Error Correction Model (VECM) to capture both the short-run dynamics and long-run equilibrium relationships among the variables. The empirical results reveal that, in the short run, inflation exerts no significant effect on unemployment, whereas zakat has a positive and significant influence, and economic growth demonstrates a negative and significant impact. In the long run, however, both inflation and economic growth have a positive and significant effect on unemployment, while zakat exhibits a negative and significant effect. These findings underscore the importance of maintaining price stability, enhancing productivity-oriented allocation of zakat, and fostering inclusive and high-quality economic growth to effectively reduce unemployment in Indonesia.